The inflexion of the Indo-European o-stems in Balto-Slavic - Kortlandt, Frederik (Baltistica, 2016)
The Balto-Slavic endings of the o‑stems were sg. nom. *‑os, acc. *‑um, neuter nom.acc. *‑o, *‑um, gen. *‑ō, dat. *‑ōi, inst. *‑oʔ, loc. *‑oi, voc. *‑e, pl. nom. *‑oi, acc. *‑oʔns, neuter nom.acc. *‑aʔ, gen. *‑um, dat. *‑omus, inst. *‑ōis, loc. *‑oisu, du. nom.acc. masc. *‑oʔ, neuter *‑oi, gen. *‑ōus, dat.inst. *‑omoʔ, loc. *‑ōu. The Balto-Slavic endings of the o‑stems were sg. nom. *‑os, acc. *‑um, neuter nom.acc. *‑o, *‑um, gen. *‑ō, dat. *‑ōi, inst. *‑oʔ, loc. *‑oi, voc. *‑e, pl. nom. *‑oi, acc. *‑oʔns, neuter nom.acc. *‑aʔ, gen. *‑um, dat. *‑omus, inst. *‑ōis, loc. *‑oisu, du. nom.acc. masc. *‑oʔ, neuter *‑oi, gen. *‑ōus, dat.inst. *‑omoʔ, loc. *‑ōu.